2005
DOI: 10.1007/s00239-004-0199-0
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Rates of Sequence Evolution of Y-Linked Satellite DNA in Rumex (Polygonaceae)

Abstract: One characteristic of sex chromosomes is the accumulation of a set of different types of repetitive DNA sequences in the Y chromosomes. However, little is known about how this occurs or about how the absence of recombination affects the subsequent evolutionary fate of the repetitive sequences in the Y chromosome. Here we compare the evolutionary pathways leading to the appearance of three different families of satellite-DNA sequences within the genomes of Rumex acetosa and R. papillaris, two dioecious plant sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(89 citation statements)
references
References 35 publications
3
86
0
Order By: Relevance
“…The evolution of these Y chromosome satellite DNAs in the non-recombining Y of R. acetosa , with a reduced rate of concerted evolution, has produced a diversification of satellite DNAs in different subfamilies and families. Two different subfamilies of the RAYSI satellite DNA are separately located in the two Ys of R. acetosa (Navajas-Perez et al, 2005b, 2006. We have isolated and characterized two other new Y-specific satellite DNA families from the genome of R. acetosa and R. papillaris , which share about 60% sequence homology with RAYSI and are located in different loci along the two Y chromosomes (B. Mariotti, S. Manzano, M. Jamilena, unpublished data).…”
Section: Tandem Satellite Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…The evolution of these Y chromosome satellite DNAs in the non-recombining Y of R. acetosa , with a reduced rate of concerted evolution, has produced a diversification of satellite DNAs in different subfamilies and families. Two different subfamilies of the RAYSI satellite DNA are separately located in the two Ys of R. acetosa (Navajas-Perez et al, 2005b, 2006. We have isolated and characterized two other new Y-specific satellite DNA families from the genome of R. acetosa and R. papillaris , which share about 60% sequence homology with RAYSI and are located in different loci along the two Y chromosomes (B. Mariotti, S. Manzano, M. Jamilena, unpublished data).…”
Section: Tandem Satellite Dnamentioning
confidence: 99%
“…1 ). The family RAE180, which is also located in a single autosomal locus, is a major component of both the Y 1 and Y 2 chromosomes (Shibata et al, 2000), while the family RAYSI is specific to the Ys of R. acetosa (Shibata et al, 1999) and other related species with a multiple sex chromosome system (XX/XY 1 Y 2 ), including R. papillari s, R. intermedius , R. thyrsoides and R. tuberosus (Navajas-Perez et al, 2005b, 2006. The evolution of these Y chromosome satellite DNAs in the non-recombining Y of R. acetosa , with a reduced rate of concerted evolution, has produced a diversification of satellite DNAs in different subfamilies and families.…”
Section: Tandem Satellite Dnamentioning
confidence: 99%
“…In fact, according to theoretical models of satellite DNA evolution and given the experimental evidence, any random sequence can lead to a family of tandem repeats. Nevertheless, the sequence relationship between different satellite DNA families found within the same genome is indicative of common origins of currently highly differentiated satellite DNAs [Navajas-Pérez et al, 2005b]. In general, it has been found that satellite repeats are generally AT rich, especially in the case of centromeric satellite DNAs.…”
Section: Satellite Dna a Family Of Sequences That Get On Well With Ementioning
confidence: 99%
“…Additionally, UGR08-F (5′-CCA ATT GGT CTC AAC TAG AACA-3′) and UGR08-R (5′-TGT TAT AGG TTT TGG ACT GCCA-3′), primers specific for the male-specific repetitive sequence RAYSII (Mariotti et al 2009) were used. Amplification with the primers R730-A (5′-CTC GGA CCA ATT ATC TCA T-3′) and R730-B (5′-CAT TAT TTG GGA GCC GAT -3′) (Navajas-Peréz et al 2005) was carried out to verify the template DNA quality. These primers amplify the repetitive RAE730 sequence that is located on the Rumex autosomes.…”
Section: Sex Ratio Analysismentioning
confidence: 99%